The Role of Richard Watson's Theological Institutes in the Development of Methodism After John Wesley - Hamilton, Barry W. (Lewiston : The Edwin Mellen Press, 2014)
No study ever before has examined the political implications of Watson's massive theological exposition. The official accounts of Methodist history mention the Theological Institutes but take their importance for granted. This work brings puts together the puzzle pieces of its major themes in a more contextualized historical interpretation.
The Role of Richard Watson's Theological Institutes in The Development of Methodism After John Wesley; Copyright Page; Dedication; Table of Contents; Foreword; Acknowledgements; Introduction; Chapter 1; Chapter 2; Chapter 3; Chapter 4; Chapter 5; Conclusion; Bibliography; Index
Description based upon print version of record.
Keywords: Methodist Church -- History; Wesley, John, -- 1703-1791.; Watson, Richard, -- 1781-1833 -- Influence; Watson, Richard, -- 1781-1833.; RELIGION / Christianity / Methodist; Electronic books